The Centers for Disease Control and Prevention: Findings From The National Healthy Worksite Program. Issue 7 (July 2017) - Lang, Jason; Cluff, Laurie; Payne, Julianne; Matson-Koffman, Dyann; Hampton, Joel
Abstract : Objective: To evaluate employers' implementation of evidence-based interventions, and changes in employees' behaviors associated with participating in the national healthy worksite program (NHWP). Methods: NHWP recruited 100 small and mid-sized employers and provided training and support for 18 months. Outcome measures were collected with an employer questionnaire, an employee survey, and biometric data at baseline and 18 months later. Results: The 41 employers who completed the NHWP implemented significantly more evidence-based interventions and had more comprehensive worksite health promotion programs after participating. Employees made significant improvements in physical activity and nutritional behaviors, but did not significantly improve employee weight. Conclusions: Training and technical support can help small and mid-sized employers implement evidence-based health interventions to promote positive employee behavior changes. A longer follow up period may be needed to assess whether NHWP led to improvements in clinical outcomes.